Teaching and learning the esoteric: an insight into how reflection may be internalised with reference to the occupational therapy profession. Issue 4 (3rd July 2016) - Wong, Ken Yan; Whitcombe, Steven W; Boniface, Gail
Abstract: This paper is concerned with the ways in which reflective practice is learnt, taught and assessed within the profession of occupational therapy. It utilises individual experiences of reflection of both students and staff members in university and practice placement settings. The discussion places reflection within learning a profession's way of being and individual learner's relation to this 'sense of being'. It concludes that the 'rote' way in which reflection is currently used to demonstrate evidence of reflective practice is detrimental to the development of a reflective professional, in this instance, an occupational therapist.